Gut macrobiotic and its metabolic pathways modulate cardiovascular disease - Zhu, Junwen; Lyu, Jin; Zhao, Ruochi; Liu, Gang; Wang, Shuangshuang (Frontiers in Microbiology, 2023)
Thousands of microorganisms reside in the human gut, and extensive research has demonstrated the crucial role of the gut microbiota in overall health and maintaining homeostasis. The disruption of microbial populations, known as dysbiosis, can impair the host's metabolism and contribute to the development of various diseases, including cardiovascular disease (CVD). Furthermore, a growing body of evidence indicates that metabolites produced by the gut microbiota play a significant role in the pathogenesis of cardiovascular disease. These bioactive metabolites, such as short-chain fatty acids (SCFAs), trimethylamine (TMA), trimethylamine N-oxide (TMAO), bile acids (BAs), and lipopolysaccharides (LPS), are implicated in conditions such as hypertension and atherosclerosis. These metabolites impact cardiovascular function through various pathways, such as altering the composition of the gut microbiota and activating specific signaling pathways.Targeting the gut microbiota and their metabolic pathways represents a promising approach for the prevention and treatment of cardiovascular diseases. Intervention strategies, such as probiotic drug delivery and fecal transplantation, can selectively modify the composition of the gut microbiota and enhance its beneficial metabolic functions, ultimately leading to improved cardiovascular outcomes. These interventions hold the potential to reshape the gut microbial community and restore its balance, thereby promoting cardiovascular health. Harnessing the potential of these microbial metabolites through targeted interventions offers a novel avenue for tackling cardiovascular health issues. This manuscript provides an in-depth review of the recent advances in gut microbiota research and its impact on cardiovascular health and offers a promising avenue for tackling cardiovascular health issues through gut microbiome-targeted therapies.